OC-110 Covered metal stent placement using santorini's duct (Minor Papilla) for pain management in chronic calcific pancreatitis – feasibility and safety. (22nd June 2015) - Sangwaiya, A; Butt, MA; Wadsworth, C; Bansi, D; Vlavianos, P; Westaby, D
Abstract : Introduction: Pain control in chronic calcific pancreatitis is often unsatisfactory. Both endoscopic and surgical drainage procedures have been described for management of intractable or recurrent severe pain. Pancreatojejunostomy has been shown to be more effective than endoscopic management (using plastic stents) of main pancreatic duct stricture (PDS). 1, 2 Fully Covered-Self expanding metal stent (FC-SEMS) placement across PDS has been assessed as a new endoscopic approach with the aim of achieving enhanced PD drainage. 3, 4 As a part of a larger series, we have identified 8 cases in which access for PD drainage has been achieved via Santorini's Duct. Method: 8 patients (M:F 3:5 mean age 58 years) had FC-SEMS placed using Santorini's Duct. 5 patients had pancreatic divisum confirmed on imaging and ERCP. 5 patients had prior placement of plastic stents and 3 had no prior endoprostheses. Planned outpatient follow up was at 3, 6 and 12 months. Mean duration of stent insertion was 3 months and response (i.e. pain control) was assessed at 3 months by using a 1–10 visual analogue scale to compare pre- and post-intervention symptoms. A score of 2 or less was classified as complete response, whereas a score of 3 or above was classified as partial response or if there was an improvement by 4 or more points in the scale. Results: FC-SEMS insertion using Santorini's Duct was feasible in all patients. The SEMS was removed at a median of 3 months (range 1.2 to 4 months). Mean follow up duration was 8.7 months. 5 patients (62.5%) reported complete response to pain while 2 (25%) had a partial response. One (12.5%) patient reported no response post endotherapy and was considered for surgical drainage. In one patient (partial response), the stricture had not resolved on FC SEMS withdrawal. A short stricture at the upstream stent margin was seen in one patient and responded to balloon dilatation. There were no instances of stent migration. Conclusion: We describe the first series reporting the use of Santorini's Duct to deliver FC-SEMS in PDS due to chronic pancreatitis. This approach is feasible, safe with early evidence of efficacy. The duration of duct patency and as a consequence success of pain management requires longer term follow up. Disclosure of interest: None Declared. References: N Engl J Med. 2007;356(7):676–84 J Gastrointest Surg. 2012;16(7):1362–9 Endoscopy 2012;44(08):784–800 Heptogastroenterology 2011;58(112):2128–31